Lost spells - Macfarlane, Robert; Morris, Jackie (Gurgaon Penguin Random House, 2020)
From Acorn to Weasel: a gorgeous, hand-illustrated, large-format spell book celebrating the magic and wonder of the natural world. All over the country, there are words disappearing from children's lives. Words like Dandelion, Otter, Bramble, Acorn and Lark represent the natural world of childhood, a rich landscape of discovery and imagination that is fading from children's minds. The Lost Words stands against the disappearance of wild childhood. It is a joyful celebration of the poetry of nature words and the living glory of our distinctive, British countryside. With acrostic spell-poems by peerless wordsmith Robert Macfarlane and hand-painted illustrations by Jackie Morris, this enchanting book captures the irreplaceable magic of language and nature for all ages.
Keywords: Nature; Nature in art